Layered double hydroxides-biopolymer nanocomposites for the controlled delivery of vitamins - El-Dessouky, Raghda El-Said (AUC Knowledge Fountain, 2016)
In this investigation, vitamin B6- and folic acid-intercalated zinc-aluminum layered double hydroxides (Zn2+/Al3+ = 3), were successfully prepared by coprecipitation (B6-LDH and Fa- LDH, respectively). Both vitamin-intercalated LDHs were characterized by XRD and FTIR analyses and compared to control pristine LDHs synthesized following the same method. The XRD analysis confirmed the structural crystallinity of the synthesized LDHs, which are typical of hydrotalcite-like materials, and confirmed the intercalation of both vitamins through the observed expansion in the LDH interlayer spacing. The FTIR analysis confirmed the presence of the vitamins in the LDH layers by observing the peaks pertaining to the vitamin-specific functional groups. The shifts of some of the peaks in the vitamin-loaded LDH from their positions in the pure vitamin’s spectrum were attributed to the existence of host-guest interactions between the vitamin and the brucite-like sheets. Such interactions are mostly hydrogen bonding and van der Waals interactions for vitamin B6, as it is expectedly intercalated in neutral form. Whereas, for folic acid, electrostatic forces are also present, since it is intercalated in its anionic form. The loading percentages were calculated to be 31.5% (w/w) for B6-LDH and 65% (w/w) for Fa-LDH. Both vitamin-intercalated LDHs were entrapped in calcium alginate matrix by the ionotropic gelation of 2.5% (w/v) sodium alginate solution comprising dispersed LDHs, in a 5% (w/v) CaCl2 solution. The gelation process produced regular spherical beads. The beads were prepared at three alginate:LDH ratios for both vitamins, which are 16:1, 10:1 and 4:1 (in order of increasing LDH content). These were labeled: B6-A/L16, B6-A/L10 and B6-A/L4 for vitamin B6 and Fa-A/L16, Fa- A/L10 and Fa-A/L4 for folic acid. The entrapment efficiency of the composite beads was evaluated indirectly by measuring the concentration of the vitamin leached in the CaCl2 solution post-gelation using UV spectroscopy. It was found that the increase in the LDH content was associated with higher entrapment efficiency of the composite beads for the vitamins, as they act as reservoirs protecting the vitamin from diffusing into the alginate matrix and leaching into the gelling solution during the curing time. XRD plots of the vitamin-loaded composite beads do not exhibit any crystalline features belonging to either the vitamin or the LDHs. The LDHs were possibly mostly de-laminated during their dispersion and gelation with alginate. The FTIR analysis of the vitamin-loaded beads was inconclusive due to the overlap of the peaks from the different components in the composite systems. The FTIR analysis of the control composite beads (A/L16, A/L10 and A/L4) and plain calcium alginate beads (A0) demonstrates the presence of the alginate-specific peaks, and the increase in the LDH-related features as the LDH content per bead increases. The broadening of the peaks belonging to the LDH’s lattice vibrations and the sharpening of the carboxylate stretching vibrations peak were attributed to the possible existence of polymer- clay interactions. Nitrogen sorption analysis of the control composite beads, the plain calcium alginate beads and the pristine LDHs characterized the texture of such materials as mesoporous. The BJH desorption average pore diameter of the pristine LDH is 18.19 nm. The increase in the LDH content per bead was found to be associated with a general decrease in porosity. The BJH desorption average pore diameter was found to decrease from 7.03 nm in A/L16 to 5.30 nm in A/L4. The decrease in pore diameter as LDH content increases in the composite beads is attributed to the possibility that the cationic LDH layers play a role in cross-linking the alginate polymer chains along with Ca2+ ions during gelation. The swelling behavior of the vitamin-loaded beads was investigated in Biorelevant simulated intestinal fluid of pH 6.5 under the same conditions used for the in-vitro release experiment. The vitamin-loaded beads were swollen appreciably and the LDH content was shown to have an influence on the swelling trend: the increase in the LDH content was associated with a decrease in the degree of bead swelling. It was proposed that such trend is due to the engagement of the cationic brucite-like sheets in a crosslinking reaction with alginate’s ionized carboxylate groups screening their repulsive forces and reducing their swelling. The in-vitro release studies were conducted so as to simulate the passage of the vitamin-loaded composite beads along the gastrointestinal tract: 2 hours in Biorelevant simulated gastric fluid (BioSGF, pH 1.6) followed by 24 hours in Biorelevant simulated intestinal fluid (BioSIF, pH 6.5). Both vitamin-loaded composite beads exhibited a substantial improvement in their stability on exposure to the acidic conditions of BioSGF, when compared to the vitamin-intercalated LDHs alone. The release profiles of the B6-loaded composite beads in BioSGF showed that increasing the LDH content per bead was associated with an increase in the relative release with time. This was attributed to the proneness of the LDHs in such beads to acid attack and their subsequent weathering, being more accessible than those comprising higher alginate content. In BioSIF, the situation was reversed, and it was shown that the release was mainly governed by the degree of bead swelling, being the least for the beads with the highest LDH content. Another factor that possibly played a role is the increased tortuosity in the composites comprising higher density of LDHs per bead. The release profiles of the folic acid-loaded composite beads in BioSGF showed that increasing the LDH content per bead was associated with a decrease in the relative release with time. Unlike B6, folic acid being less soluble in the acidic medium, its dissolution becomes the limiting factor, and the release of the dissolved folate ions becomes dominated by their diffusivity in the alginate matrix. The LDH layers endow the matrix with barrier properties, and the bulky folate ions have to adopt longer and more tortuous pathways in order to be released, explaining the reduced relative release with time as the LDH content increases per bead. In BioSIF, the beads of the highest LDH content show the highest relative release with time, owing to the repulsive forces between the ionized folate and alginate’s carboxylates in basic conditions, which are more pronounced in the high LDH content (and thus folate) beads. We believe that samples B6-A/L16 and Fa-A/L4 show the most promising features of efficient oral controlled-release drug delivery systems, with satisfactory sustained release properties.